A new species of Pavonia (Malvaceae, Malvoideae) from Mato Grosso, Brazil - Rondon-Anjos, Marcos Vinicius; Coutinho, Thales Silva; Koch, Ana Kelly (Phytotaxa, 2025)
Pavonia neuropetala, a new species from the Cerrado of southwestern Mato Grosso, is hereby described and illustrated. It belongs to Pavonia subgenus Pavonia section Lopimia f and its conservation status was assessed as Critically Endangered. Its morphological affinities with related species are discussed, images, a table with morphologic data, and a key of species from Pavonia section Lopimia from Mato Grosso are provided.